Determinants of Moral Courage Including the Role of Workplace Conditions, Grief Support, and Salary Among Surgical Nurses in Jiaxing Tertiary Class A Hospitals: A Cross-Sectional Analysis - Cheng HY; Pu FY; Li XP; Wu LF (Journal of Multidisciplinary Healthcare)
Hai-Ying Cheng,1 Feng-Yan Pu,1 Xiao-Ping Li,2 Ling-Fang Wu3 1Department of Nursing, The Second Affiliated Hospital of Jiaxing University, Jiaxing, Zhejiang, 314000, People’s Republic of China; 2Department of Surgery, The Second Affiliated Hospital of Jiaxing University, Jiaxing, Zhejiang, 314000, People’s Republic of China; 3Department of Otorhinolaryngology, The Second Affiliated Hospital of Jiaxing University, Jiaxing, Zhejiang, 314000, People’s Republic of ChinaCorrespondence: Ling-Fang Wu, Department of Otorhinolaryngology, The Second Affiliated Hospital of Jiaxing University, No. 1518 of Huancheng Road, Nanhu District, Jiaxing, 314000, People’s Republic of China, Tel +86 13957383389, Email wulf_fang@outlook.comObjective: This study aims to evaluate moral courage among surgical nurses and examine its association with factors such as decent work and professional grief support, to inform nursing management strategies for enhancing moral courage.Methods: A cross-sectional study included convenience sample of 431 surgical nurses from municipal tertiary Class A hospitals, with 406 valid responses generated after exclusions. Data on demographics (gender, age) and professional characteristics (years of experience, marital status, child-bearing status, education level, professional title, administrative role, employment type, monthly income, and frequency of night shifts) was collected. Participants were required to respond to validated scales measuring moral courage, perceptions of workplace conditions, and grief support. Multiple linear regression analysis was conducted to identify factors associated with moral courage.Results: The mean moral courage was assessed by Chinese version of the Nurses’ Moral Courage Scale (NMCS) with average score of 80.04 ± 14.28 (maximum possible score = 105). Workplace conditions, grief support, and monthly salary emerged as significant associated factors, collectively explaining 42.0% of the total variance in moral courage scores (F = 16.528, model p < 0.001).Conclusion: Surgical nurses in this study demonstrated moderate to high levels of moral courage. Key factors included workplace conditions, access to grief support systems, and monthly salary. Nursing management strategies should prioritize enhancing professional values, provide career development assistance, offering emotional support, and fostering a positive work environment to further strengthen moral courage among surgical nurses.Keywords: decent work, grief support, moral courage, nurses, surgery